Meta-analysis: Confidence intervals and Prediction intervals - Botella, Juan; Sánchez-Meca, Julio (Anales de Psicología / Annals of Psychology, 2024)
Several types of intervals are usually employed in meta-analysis, a fact that has generated some confusion when interpreting them. Confidence intervals reflect the uncertainty related to a single number, the parametric mean effect size. Prediction intervals reflect the probable parametric effect size in any study of the same class as those included in a meta-analysis. Its interpretation and applications are different. In this article we explain their different nature and how they can be used to answer specific questions. Numerical examples are included, as well as their computation with the metafor R package.